2015
DOI: 10.1259/bjr.20150458
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in the staging of breast cancer patients: does histological type and molecular subtype matter?

Abstract: The real benefit of MRI for treatment planning in patients with breast cancer may be different according to the histological type and molecular subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(33 reference statements)
2
5
0
Order By: Relevance
“…Our sample of HER2 overexpressing breast carcinomas was composed of large tumours, with high rates of multifocality as well as suspicious axillary lymph nodes, which is consistent with the literature [ [17] , [18] , [19] ]. In our study, the pCR rate among patients determined to be HER2+ by IHC was 65%, compared to 22% among patients in the FISH group, similar to the results of other investigators [ 4 , 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our sample of HER2 overexpressing breast carcinomas was composed of large tumours, with high rates of multifocality as well as suspicious axillary lymph nodes, which is consistent with the literature [ [17] , [18] , [19] ]. In our study, the pCR rate among patients determined to be HER2+ by IHC was 65%, compared to 22% among patients in the FISH group, similar to the results of other investigators [ 4 , 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…PR‐positivity is usually associated with a luminal A molecular subtype. This is consistent with a study looking at MRI size and histological and molecular subtype, which found that correlation between primary tumor size on MRI and size as determined on surgical pathology was better for luminal A and triple‐negative molecular subtypes than for luminal B and HER 2 molecular subtypes 26 . This may explain the association for PR‐positivity and biopsy‐proven contralateral cancers in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a study looking at MRI size and histological and molecular subtype, which found that correlation between primary tumor size on MRI and size as determined on surgical pathology was better for luminal A and triple-negative molecular subtypes than for luminal B and HER 2 molecular subtypes. 26 This may explain the association for PR-positivity and biopsy-proven contralateral cancers in the current study. Although we did not find a similar association in the triplenegative patients, this may be due to the overall small percentage of triple-negative patients included in our patient population.…”
Section: Factors Associated With Detection Of Occult Cancermentioning
confidence: 58%
“…And the four major subtypes luminal A, luminal B, HER2-overexpressed and triple-negative breast cancer (TNBC) were defined. Magnetic resonance imaging (MRI), a noninvasive and high sensitive examination, has been increasingly used in the assessment of breast disease, including the differential diagnosis of benign and malignant lesions, preoperative evaluation, pretreatment planning and efficacy prediction 5 , 6 . The correlation between the MRI morphology as well as dynamic features and the molecular subtypes of breast cancer have been reported 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…But most previous studies were based on describing the findings using a lexicon by the radiologist subjectivly. Although most of lexicon is accepted generally, it turned to be variable with different observer 6 , 9 . Quantitative analysis of the MRI dynamic features in breast cancer had been reported 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%